Towards a Sustainable Blue Economy for Namibia and Its Coastal Communities: A Contemporary Socio-Legal Perspective - Chiedza Machaka; Tapiwa V Warikandwa (Potchefstroom Electronic Law Journal)
Namibia's sustainable blue economy plan is influenced by the recognition that the typical single sector regulation approach to the aquatic ecosystem lacks synergies and coordination. The Blue Economy Agenda is a policy instrument for unifying and regulating economic activity for the benefit of Namibian citizens. The policy that provides for integrated sustainable management of the aquatic ecosystem seeks social inclusion, equitable distribution of natural resources, and prosperity for the public benefit. Such resource utilisation must be done in a way that promotes environmental health and sustainability. Namibia has laws in place that seek to regulate the blue economy and to ensure that policy objectives are met. However, such laws, in particular the Marine Resources Act 27 of 2000, exclude the recognition of marginalised coastal communities and small-scale fisheries sector from their scope. This exclusion is likely to undermine the need to promote social inclusion, the equal sharing of benefits, and of access to marine resources. This article addresses the prospects and challenges of fully utilising Namibia's aquatic ecosystems to meet the country's developmental agenda. Written from a socio-legal perspective, the article will argue for an integrated and/or comprehensive strategy to achieving a sustainable blue economy that is inclusive and beneficial to all Namibians, including the marginalised coastal communities and the small-scale fisheries.